Coping with challenges of resources, environment and climate change through agrifood system transformation: experiences from China and Africa - Ming, Lei; Ting, Meng; Zhiyao, Yang; Jingjing, Shan; Ouedraogo, Issa (HEP Journals, 2025)
Agrifood systems in China and Africa are subject to increasing pressures due to resource limitations, environmental degradation and climate change. Both regions confront challenges such as soil degradation, water scarcity and biodiversity loss, while also experiencing the adverse impacts of climate change on agricultural productivity and food security. This paper examines these challenges and outlines strategic actions with a systems approach being taken in both regions to transform their agrifood systems. Key strategies include enhancing agricultural efficiency, strengthening resilience to climate-related shocks, and promoting sustainability through innovative practices. Also, the paper emphasizes the importance of China–Africa cooperation in climate-smart production, trade and market optimization, and sustainable diets. The role of China–Africa food policy network in supporting these efforts are also discussed. The paper concludes with a call for continued collaboration to facilitate the sustainable transformation of agrifood systems in developing countries, particularly in China and Africa, ensuring food security and resilience for the future.